RESPON PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays-saccharata Sturt) PADA APLIKASI JUMLAH BENIH DAN PUPUK MAJEMUK DI KOTA YOGYAKARTA - Irawan; Maria Theresia, Darini; Sri, Widata (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the use of the right number of seeds and doses on NPK fertilizer on the growth and yield of sweet corn plants and to determine the interaction between the number of seed and to the dose of compound fertilizer on the growth and yield of sweet corn plants. The research was conducted from June to December 2022 in Giwangan, Umbulharjo, Yogyakarta. The research is arranged in RAKL with two factors. The first factor is the number of seeds per planting hole, namely on seed per planting hole (D₁), and two seeds per planting hole (D₂). the second factor is the dose of compound fertilizer, namely the dose of NPK fertilizer 100 kg/ha (N₁), 150 kg/ha (N₂), and 200 kg/ha (N₃). The variables observed consisted of growth variables, such as average plant heigh, number of leaves per plant, leaf area of the plantation, chorophyll content, fresh weight per plant, dry weight per plant and yield variables such as fresh weight per plant, dry weight per plant, weight brown cobs, weight of brown cobs per hectare, number of leaves per plant, cob diameter, number of rows of seeds on cob, sweetness level. Observational data were analyzed using variance at the 5% level followed by the DMRT test at a = 5% level. The results of the analysis showed that there was no interaction between the number of seeds per planting hole and the dose of compound ferlizer on the growth and yield of sweet corn plants. The treatment of the number of seeds per planting hole showed an effect on growth, the number of two seeds per hole gave lower yields than the number of one seed per planting hole. Doses of 100 kg, 150 kg, 200 kg NPK fertilizer had no effect on the growth and yield of cob weight and fresh weight of sweet corn plants. The treatment of the number of seeds per planting hole and the application of NPK fertilizer showed a significant and higher difference with the control on growth and yield. Keywords : sweet corn, number of seeds, NPK fertilizer, growth and yield.